Electrical Potential Distribution in Polymethyl Methacrylate-Graphene Oxide Nanocomposites - Zainuddin Nawawi; R. F. Kurnia; N. F. A. Isa; Z. Buntat; D. R. Yuniarti; M. I. Jambak; Muhammad Abu Bakar Sidik (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Research work of polymer nanocomposites in high voltage insulator becomes interest nowadays. Polymer based and nanofillers are the core components in polymer nanocomposites. By adding such a big amount of nanofiller it would enhance the electrical and mechanical properties of polymers.  However as for today, a little percentage of nanofiller concentration could dramatically enhanced the properties of the polymeric material. Recent research of graphene oxide (GO) nanofiller has brought to this project interest.  This paper presents several methods that have been published to development PMMA (poly methyl methacrylate)/GO nanocomposites and a simulation of PMMA/GO in order to investigate the potential distribution.